Pengembangan Media Pembelajaran Powerpoint Interaktif Tema Hujan Asam Yang Berorientasi Pada Keterampilan Komunikasi Sains Siswa Kelas VII - Dhea amelia Amelia; Liska Berlian; Lukman Nulhakim (PendIPA Journal of Science Education, 2022)
Communication skills are one of the skills included in 21stCentury Skills. One way that can be done to grow communication skills is to develop interactive powerpoint media oriented to science communication skills which requires students to be skilled in communicating research results, developing scientific attitudes, and increasing student activity in learning. The purpose of this study was to develop and determine the level of validity of interactive powerpoint learning media on the theme of acid rain which is oriented to the science communication skills of class VII students. This research is included in development research with 4D models, but in this study only uses 3 stages, namely: define, design, and development. The instrument used in this study was a validation sheet filled out by 2 expert lecturers from FKIP Untirta and 3 science teachers at junior high school. The research instruments used were interview sheets and validation questionnaires. The results showed that the interactive powerpoint media developed was included in the Valid category with a percentage value of 79.94%. The results of the validation of material experts obtained a percentage value of 77.00% with valid criteria, media experts 82.81% with very valid criteria and 80.02% junior high school science teachers with valid criteria. Based on the recapitulation of the validation results that have been carried out by all validators of learning media in the form of interactive powerpoints oriented to students' science communication skills on the acid rain theme, it can be tested in science learning activities.